2011
DOI: 10.3389/fnsyn.2011.00001
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Signaling and Aberrant RNA Splicing in Autism Spectrum Disorders

Abstract: Interactions between presynaptic and postsynaptic cellular adhesion molecules (CAMs) drive synapse maturation during development. These trans-synaptic interactions are regulated by alternative splicing of CAM RNAs, which ultimately determines neurotransmitter phenotype. The diverse assortment of RNAs produced by alternative splicing generates countless protein isoforms necessary for guiding specialized cell-to-cell connectivity. Failure to generate the appropriate synaptic adhesion proteins is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 97 publications
2
36
0
Order By: Relevance
“…This is consistent with previous results showing that genes associated with transcriptional regulation were downregulated in ASD 48. It has been well established that epigenetic and post‐transcriptional regulation have pivotal roles in the pathogenesis of neurodevelopmental disorders, including ASD 49. In agreement with this finding, genome‐wide transcriptomic analysis identified differential splicing events in post‐mortem ASD brains, which were associated with neuronal activity‐dependent gene regulation 50.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous results showing that genes associated with transcriptional regulation were downregulated in ASD 48. It has been well established that epigenetic and post‐transcriptional regulation have pivotal roles in the pathogenesis of neurodevelopmental disorders, including ASD 49. In agreement with this finding, genome‐wide transcriptomic analysis identified differential splicing events in post‐mortem ASD brains, which were associated with neuronal activity‐dependent gene regulation 50.…”
Section: Discussionsupporting
confidence: 92%
“…2, namely 1) MECP2 influences global translation by enhancing the AKT/mTOR signaling pathway [46], 2) Alternative splicing of downstream gene products is affected because MECP2 forms a complex with YB1, an important splicing factor [29, 4751], 3) Expression of various microRNAs and long non-coding RNAs is regulated by MECP2 (20, 45, 47–49), and 4) MECP2 triggers the chromatin compaction at methylated DNA sites which regulates the transcription of adjacent genes (34, 37–41). The last one is an important (and best investigated) pathway and will be explained in detail below.…”
Section: Mecp2 Functionmentioning
confidence: 99%
“…Recently, it has also been shown that the DNA methylation-dependent binding of MeCP2 to exonic sequences modulates alternative splicing (Maunakea et al 2013). Altered RNA splicing of synaptic genes have been reported in autism as well as Rett syndrome (Smith and Sadee 2011). However, whether MeCP2 plays a role in RNA splicing in autism is currently unknown.…”
Section: Mecp2 In Rna Splicingmentioning
confidence: 99%